Comparison of mean duration of two-segment regression time in patients undergoing lower limb surgery treated with combined spinal-epidural anaesthesia vs. Combined spinal-epidural anaesthesia plus epidural volume extension with saline - Komal Javaid, Anum Zeb, Mudassar Aslam, Muhammad Abdul Rehman Afzal, Athar Adnan Uppal, Fareeha Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Combined spinal-epidural (CSE) anesthesia is a novel technique that decreases the amount of anesthetic required yet with greater anesthetic effect compared to spinal or epidural anesthesia alone. Recent studies showed that epidural volume extension (EVE) with saline further increased the anesthetic effect of this combined approach resulting in longer two-segment regression time. However, literature was scarce in the local context that provides the basis of the present study. Aim: The study focuses on the comparison between the mean duration of two-segment regression time in patients who underwent lower limb surgery treated with CSE and CSE plus EVE with saline. Methods: It was a randomized controlled trial and included 60 patients of both genders who range between 20-60 years. They belong to ASA class I and II and underwent lower limb trauma surgery with CSE anesthesia which were further randomly divided into two treatments groups. The patients of Group-A received EVE in addition to standard CSE while Group-B received standard CSE alone. The outcome variable was the mean two-segment regression time which was compared in these two groups. Results: Mean age of selected patients was 35.75±10.60 years. Study included 35 (58.3%) male and 25 (41.7%) female patients. The mean duration of surgery was 79.65±12.92 minutes while the mean BMI was 27.78±3.25 Kg/m2. Nineteen (31.7%) patients were from ASA Class-I and 41 (68.3%) patients associated with ASA Class-II. The mean two-segment regression time was substantially longer in the CSE plus EVE group as compared to the group receiving CSE alone (83.77±7.56 vs. 59.97±6.22 minutes; p-value<0.001). In these two groups, a statistically important difference was also noted across subgroups based on the age of the patient, gender, BMI, duration of surgery, history of diabetes and ASA status. Conclusion: CSE anesthesia with EVE proved its superiority over the conventional practice of CSE alone in terms of longer mean two-segment regression time in patients with lower limb trauma surgery.